Lifelong Voluntary Exercise Modulates Age-Related Changes in Oxidative Stress - Bouzid, Mohamed Amine; Filaire, Edith; Matran, Régis; Robin, Sophie; Fabre, Claudine (International Journal of Sports Medicine, 2018)
The hypothesis that aging and regular physical activity could influence oxidative stress has been studied by comparing antioxidant activities (superoxide dismutase (SOD), glutathione peroxidase (GPX), glutathione reductase (GR), ascorbic acid and α-Tocopherol) and malondialdehyde level (MDA) in four groups: young sedentary (n=15; age: 20.3±2.8 years; YS), young active (n=16; age: 21.4±1.9 years; YA), old sedentary (n=15; age: 65.1±3.5 years; OS) and old active (n=17; age: 67.2±4.8 years; OA). Antioxidant activities and MDA level were assessed at rest and after an incremental exercise. There was no difference in resting antioxidant activities and lipid peroxidation between YS and OS. However, resting SOD and GR activities were higher in YA compared to OA (p<0.01 and p<0.05, respectively) and resting MDA level was higher in OA compared to YA (p<0.01). After exercise, a significant increase in SOD and GPX activities was observed in YS, YA and OA (p<0.01). Likewise, after exercise a significant increase of MDA level in YA, OS and OA (p<0.01) was observed. In addition, the comparison of YA to OA and YS to OA revealed similar antioxidant activities and lipid peroxidation between YS and OA, whereas antioxidant activities were higher in YA compared to OA. These data suggest that beneficial effects of regular physical activity in antioxidant defense and lipid peroxidation damage could be impaired by the aging process and that regular physical activity in older adults could maintain age-related decreases in antioxidant defense.
Keywords: aging; oxidative stress; exercise; physical activity